Body and Body Psychotherapy in the Global Village - Helferich, Christoph (Bioenergetic Analysis, 2015)
The reality of the Global Village profoundly influences body psychotherapy, challenging fundamental received concepts such as «nature”, «body” and «personal identity”. This paper investigates these changes, particularly developing three points: a) the concepts of «body” and «nature” in the founding fathers of body psychotherapy; b) the challenge to these concepts by developments in advanced technology and virtual communication; c) the task of body psychotherapy today – namely – to raise awareness of the importance of both the external «nature” around us and our internal, bodily «nature”, both of which can no longer be taken for granted, but must become the object of our choices and lifestyles. In the clinical considerations section the author presents a technique of «nurturing contact” that allows the patient’s deep experience of his own bodily essence.